A review of the siphonophore species mentioned in Haeckel’s (1888b) Challenger Monograph - Pugh, P.r. (Zootaxa, 2019)
In his Challenger Monograph Haeckel (1888b) listed a total of 204 species of siphonophores and 36 species of Porpitidae (Disconectae, according to Haeckel), which are now known not to belong to the Siphonophorae. In this paper the siphonophore species have been divided into four categories: a). species that had been described previously by an acknowledged authority other than Haeckel; b). species where Haeckel changed the generic or specific name of a previously described species by another authority, and then ascribed the authority to himself; c). species that Haeckel actually described and illustrated as what he believed to be new; and d). species that Haeckel mentioned in the text as a new species, but with the description deferred to a later publication or simply not given. The validity of the forty-three species that Haeckel actually described is then discussed. A full list of all these species is given in an Appendix.